Enhancing Adolescent Awareness on Safe Cosmetic Use: A Community Education at Santa Patricia High School, Tangerang - Putriana Rachmawati; Nicky Nathanael; Jessica Christy Hamzah; Nathaniel Leslie; Sabrina Jovita Bunawan; Sharon Susanto; Yulius Evan Christian (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Cosmetics are products designed for use on the external parts of the human body to clean, alter appearance, provide fragrance, improve body odor, or maintain health. The cosmetic industry in Indonesia has experienced significant growth. Technology and beauty stereotypes disseminated through social media have influenced the increasing demand for cosmetics among teenagers. Research shows that 45.4% of teenagers in Indonesia use skincare products before the age of 19, and 46% experience skin health issues due to unsafe products. The Community Service Program aims to enhance teenagers' knowledge about safe cosmetics. This program was conducted through interactive lectures and a peel-off mask-making workshop at Santa Patricia High School in Tangerang, involving 72 students from 10th and 11th grades. Evaluation was performed through pretests and posttests, showing a 16% increase in participants' knowledge. A total of 82% of participants achieved good scores in the posttest. Additionally, 97% of participants understood the material presented, and 99% were satisfied with the overall event. This educational initiative successfully increased students' awareness and knowledge about the safety of cosmetic use, providing new insights into safe ingredients and steps for choosing appropriate cosmetics. Similar activities are encouraged to broaden teenagers' understanding of cosmetic safety.